Who's in the hood? Assessing a novel rodent deterrent at pest fencing in New Zealand. Issue 3 (2nd July 2020) - Farnworth, Bridgette; Innes, John; Kelly, Catherine; Waas, Joseph R.
ABSTRACT: Fenced ecosanctuaries may reduce predator presence at reserves by incorporating deterrents into pest management programmes. We quantified rodent visits to the steel hood of ecosanctuary fencing and illuminated our experimental sites to assess whether light could deter ship rats ( Rattus rattus ) and house mice ( Mus musculus ). Additionally, we assessed how mice used fencing in the presence and absence of ship rats by utilising two types of fence sections: one accessible to mice alone (along fencing within an ecosanctuary) and one accessible to mice and rats (at perimeter fence sites opposite pasture or forest habitat). We monitored sites using cameras and tracking cards within the fence hood and at tunnels at the fence base. Along the internal fence, mice were never observed within the hood but marked 40% of tunnels at the fence base. Along the perimeter fence, mice made four visits to the hood and marked 28% of tunnels at the fence base. Rats travelled exclusively within the fence hood ( n  = 42). Light did not reduce rat sightings but adjacent habitat affected their presence (forest > pasture; p  ≤ 0.01). Positioning future ecosanctuary fencing alongside pasture and maintaining open corridors opposite fences at current ecosanctuaries may reduce rat presence.